2013
DOI: 10.1063/1.4794809
|View full text |Cite
|
Sign up to set email alerts
|

Titanium catalyzed silicon nanowires and nanoplatelets

Abstract: Silicon nanowires, nanoplatelets, and other morphologies resulted from silicon growth catalyzed by thin titanium layers. The nanowires have diameters down to 5 nm and lengths to tens of micrometers. The two-dimensional platelets, in some instances with filigreed, snow flake-like shapes, had thicknesses down to the 10 nm scale and spans to several micrometers. These platelets grew in a narrow temperature range around 900 celsius, apparently representing a new silicon crystallite morphology at this length scale.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(42 reference statements)
0
4
1
Order By: Relevance
“…A confusing phenomenon in the experiment of Lin et al 36 is that uniaxial stress of 10 MPa has an even stronger effect than that of 15 MPa, which is still need to be verified. In contrast, other experimental results 5,33,34 indicate that a heavier load leads to a stronger effect.…”
Section: B Effect Of Constant Strain On Oxide Stress and Scale Thickcontrasting
confidence: 49%
See 3 more Smart Citations
“…A confusing phenomenon in the experiment of Lin et al 36 is that uniaxial stress of 10 MPa has an even stronger effect than that of 15 MPa, which is still need to be verified. In contrast, other experimental results 5,33,34 indicate that a heavier load leads to a stronger effect.…”
Section: B Effect Of Constant Strain On Oxide Stress and Scale Thickcontrasting
confidence: 49%
“…This is different from lots of experimental results in which tensile strain loads have a promoting effect. 5,31,33,34 As seen in Fig. 7(a), scale thickness under tensile stress load is still generally higher than that under compressive load, indicating that the oxidant diffusion process is actually accelerated by tensile loads.…”
Section: B Effect Of Constant Strain On Oxide Stress and Scale Thickmentioning
confidence: 58%
See 2 more Smart Citations
“…It has been found that, in GaNBiAs semiconductor alloy, when the N : Bi composition ratio is 0.58 we can obtain lattice matching with GaAs 5 . Co-alloying N and Bi opens up avenues for bandstructure engineering and precise strain control in the GaNBiAs quaternary alloy 6 . In dilute-Bi alloys, the a) Electronic mail: sumanta001@e.ntu.edu.sg b) Electronic mail: edhzhang@ntu.edu.sg bandgap reduction is caused due to coupling between Biresonant state and the valence band (VB) state; while on the other hand, in dilute-N alloys, this effect is induced due to N-resonant state coupling with conduction band (CB) state 7 .…”
Section: Introductionmentioning
confidence: 99%